The lncRNA VELUCT strongly regulates viability of lung cancer cells despite its extremely low abundance - Seiler, Jana; Breinig, Marco; Caudron-Herger, Maïwen; Polycarpou-Schwarz, Maria; Boutros, Michael; Diederichs, Sven (Nucleic acids research, 2017)
Little is known about the function of most non-coding RNAs (ncRNAs). The majority of long ncRNAs (lncRNAs) is expressed at very low levels and it is a matter of intense debate whether these can be of functional relevance. Here, we identified lncRNAs regulating the viability of lung cancer cells in a highthroughput RNA interference screen. Based on our previous expression profiling, we designed an siRNA library targeting 638 lncRNAs upregulated in human cancer. In a functional siRNA screen analyzing the viability of lung cancer cells, the most prominent hit was a novel lncRNA which we called Viability Enhancing LUng Cancer Transcript (VELUCT). In silico analyses confirmed the non-coding properties of the transcript. Surprisingly, VELUCT was below the detection limit in total RNA from NCI-H460 cells by RT-qPCR as well as RNA-Seq, but was robustly detected in the chromatin-associated RNA fraction. It is an extremely low abundant lncRNA with an RNA copy number of less than one copy per cell. Blocking transcription with actinomycin D revealed that VELUCT RNA was highly unstable which may partially explain its low steady-state concentration. Despite its extremely low abundance, loss-of-function of VELUCT with three independent experimental approaches in three different lung cancer cell lines led to a significant reduction of cell viability: Next to four individual siRNAs, also two complex siPOOLs as well as two antisense oligonucleotides confirmed the strong and specific phenotype.
Gesehen am 17.10.2018